Emergence of extended-spectrum beta-lactamases-producing Escherichia coli in community-acquired urinary infections in Casablanca, Morocco - Fatna Bourjilat; Brahim Bouchrif; Noureddine Dersi; Jean David Perrier Gros Claude; Hamid Amarouch; Mohammed Timinouni (Journal of Infection in Developing Countries)
Introduction: Extended-spectrum beta-lactamase- (ESBL)-producing Escherichia coli are an increasingly significant cause of community-acquired infection worldwide. The aim of this study was to assess the prevalence of ESBL-producing E. coli in a community, to analyze the relationship between strains studied, and to characterize the ESBL genes involved in this resistance.